Aspergilosis Kutis Primer dengan Gambaran Klinis Menyerupai Tuberkulosis Verukosa Kutis - Dani, Adinda Amalia; Widasmara, Dhelya (RSUD Dr. Saiful Anwar Province of East Java, 2022)
Background: Primary cutaneous aspergillosis (PCA) is a rare invasive fungal infection of the skin that can be life-threatening. This disease is caused by Aspergillus spp and belongs to the deep mycosis (subcutaneous) group. Case report: A 63-year-old man came with complaint of wound that feels itchy, painful and exudative on right lower leg since 5 years ago. Dermatological examination showed multiple erythematous papules and plaques with verrucous surface partially covered in brownish yellow crust accompanied by xerosis and some ulcers with pus. The proposed differential diagnoses are Tuberculosis verrucosa cutis, Chromoblastomycosis and Mycetoma. The result of tissue culture showed Aspergillus niger. Biopsy result supports the diagnose of deep mycosis. The patient then diagnosed as primary cutaneous aspergillosis, treated with pulse dose Itraconazole and improved clinically within 2 weeks. Conclusion: Atypical manifestation in this patient gives diagnostic challenge for dermatologist. The importance of establishing diagnosis in patient with deep mycoses are to identify the cause, determine the appropriate treatment and prevent cimplication.